MAÞiR Words - Språkbanken Text (University of Gothenburg, 2024)
Mathir Words contains lemmata extracted from digitized versions of
Söderwall's dictionary. The information consists of a lemma, with
part-of-speech indication. The resource was compiled as part of the
Mathir project, financed by the Marcus and Amalia Wallenberg Foundation,
no. 2012.0146, by Gerlof Bouma and Yvonne Adesam.

Mathir Ord innehåller lemman extraherade från en digitaliserad version av
Söderwalls ordbok. Informationen består av lemma och ordklassinformation.
Resursen sammanställdes inom projektet Mathir, finansierat av Marcus och
Amalia Wallenbergs Minnesfon, nr. 2012.0146, av Gerlof Bouma och Yvonne
Adesam.
MAÞiR Ord
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik